THE REPRESENTATION OF WOMEN AS VICTIMS OF MASCULINE POWER IN CANTIK ITU LUKA BY EKA KURNIAWAN: AN EXISTENTIALIST FEMINIST STUDY - Febriyanti, Weni; Suaedi, Hasan; Afrizal, Mohamad (Universitas Islam Sumatera Utara (UISU), 2025)
This study analyzes the representation of women as victims of masculine power in Cantik Itu Luka by Eka Kurniawan through the lens of Simone de Beauvoir’s existentialist feminism. The novel was chosen for its intricate portrayal of women’s suffering and social positioning within Indonesia’s patriarchal structure, marked by violence, sexuality, and moral oppression. While earlier research has explored themes of women and patriarchy in Kurniawan’s works, studies explicitly connecting Cantik Itu Luka to Beauvoir’s existentialist feminist theory remain scarce. This study therefore contributes to a deeper understanding of women’s freedom and existence in Indonesian literature. Employing a qualitative descriptive approach, the research draws on the text of Cantik Itu Luka as the primary data source. Analysis is conducted through close reading of narrative elements, symbols, and character actions, framed by Beauvoir’s concepts of freedom, oppression, and woman as the “Other.” The findings reveal that masculine power in the novel manifests through physical violence, sexual exploitation, and moral or social control over women’s bodies. The protagonist, Dewi Ayu, together with other female characters such as Alamanda and Maya Dewi, embodies the subjugation of women under patriarchy. Yet, amid this suffering emerges an existential awareness that urges women to assert freedom and autonomy as self-determining subjects. Through his use of magical realism, Kurniawan captures the tension between oppression and resistance, illuminating women’s search for meaning and agency. Ultimately, this study enriches feminist literary criticism in Indonesia by showing how literature reflects women’s existential struggles toward liberation and self-sovereignty.